Evaluation of the immunohistochemical expression of HER2/NEU in urinary bladder neoplasms in a tertiary care hospital - Samra, Sukhmani; Nibhoria, Sarita; Sandhu, Vaneet Kaur; Singh, Amandeep (International Journal of Research in Medical Sciences, 2023)
Background: HER2/NEU expression in urothelial neoplasms has been reported to range from 9% to 80% on immunohistochemistry. We studied the expression of HER2/NEU in urothelial neoplasms and its variability according to histological grade along with the prognostic value. Methods: The present study was conducted on 60 formalin-fixed, paraffin-embedded specimens of urinary bladder neoplasms, which comprised 45 cases of high-grade urothelial carcinoma followed by 13 cases of low-grade and 2 cases of PUNLMP. These were then subjected to IHC by HER2/NEU. Membrane positivity for HER2/NEU was noted. Results: A total of 65% of cases showed positive membranous HER2/NEU expression. HER2/NEU expression was noted in 82.6% of cases of high grade while 8.4% of cases of low grade were positive for HER2/NEU expression. Conclusions: The majority of high grade invasive urothelial carcinomas showed positive HER2/NEU expression with a significant p-value <0.001. Thus patients with high grade urothelial carcinoma may benefit from HER2/NEU targeted therapy.